Phase-dependence of elbow muscle coactivation in front crawl swimming - Lauer, J.; Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J.; Rouard, A. H. (Journal of Electromyography and Kinesiology, 2013)
Propulsion in swimming is achieved by complex sculling movements with elbow quasi-fixed on the antero-posterior axis to transmit forces from the hand and the forearm to the body. The purpose of this study was to investigate how elbow muscle coactivation was influenced by the front crawl stroke phases. Ten international level male swimmers performed a 200-m front crawl race-pace bout. Sagittal views were digitized frame by frame to determine the stroke phases (aquatic elbow flexion and extension, aerial elbow flexion and extension). Surface electromyograms (EMG) of the right biceps brachii and triceps brachii were recorded and processed using the integrated EMG to calculate a coactivation index (CI) for each phase. A significant effect of the phases on the CI was revealed with highest levels of coactivation during the aquatic elbow flexion and the aerial elbow extension. Swimmers stabilize the elbow joint to overcome drag during the aquatic phase, and act as a brake at the end of the recovery to replace the arm for the next stroke. The CI can provide insight into the magnitude of mechanical constraints supported by a given joint, in particular during a complex movement.